Milk metabolite composition of a semi-captive population of Asian elephants - Galante, Laura; dos Santos; Diogo Joao Franco; Mikkonen, Elisabeth; Horak, Jeannie; Stijepic, Zorica; Demmelmair, Hans; Vielhauer, Andrea; Koletzko, Berthold; Zaw, Htet Thi; Htut, Win; Lummaa, Virpi; et al. (ROYAL SOC, 2025)
Lack of maternal milk commonly leads to Asian elephant calves' death in captivity. Currently, available supplements seem inefficient. Hence, we aimed at characterizing the composition of Asian elephant milk to provide information on calves' nutritional needs. Seventy milk samples from 22 Asian elephants living in semi-captivity in their natural environment in Myanmar were collected. Samples were analysed through various techniques including liquid chromatography tandem mass spectrometry, gas chromatography-flame ionization detector, and bicinchoninic acid assay to determine total protein content and various metabolites. Associations with lactation stage (months postpartum) were investigated through repeated measure mixed models. We identified 160 compounds: 22 amino acids, 12 organic acids of the tricarboxylic acid cycle, 27 fatty acids, 15 acyl-carnitines and 84 phospholipids. The milk contained substantial amounts of free glutamate (median: 1727.9, interquartile range (IQR): 1278.4 mu mol l-1) and free glycine (2541.7, IQR: 1704.1 mu mol l-1). The fatty acid profile was mostly constituted by saturated fatty acids, particularly capric acid (40.1, IQR: 67.3 g l-1). Milk samples also contained high amounts of carnitines, phospholipids and organic acids. The wide array of metabolites identified and quantified, some of which present high concentrations in the milk from this species as opposed to other species, suggests underpinning physiological functions that might be crucial for the survival of Asian elephant calves.